RANCANG BANGUN SISTEM DETEKSI GERAKAN MANUSIA UNTUK OTOMATISASI AIR CONDITIONING BERBASIS ARDUINO - Diani Muslimah Baharudin (JURNAL PERANGKAT LUNAK, 2022)
ABSTRACTA device called an air conditioner (AC) is used to cool and control humidity in an enclosed space. However, there is still a lot of wasted use, such as failing to turn off the air conditioner (AC) when leaving the room, which makes the current way of using the air conditioner (AC) ineffective. As a result, we need the right technology to solve this problem. Design and build human detection system for Arduino based automation system for AC. This tool is used to detect human movement and control the room air conditioner remotely based on web and Arduino. Box-shaped hardware with Arduino Nano as the main controller of the system, PIR sensor as motion detection input, and DHT11 as temperature and humidity sensor.Keyword : Arduino Nano, PIR Sensor, DHT11 Sensor, IoT